Development of a computer-tailored nutrition and physical activity intervention for lower-educated women of Dutch, Turkish and Moroccan origin using content matching and ethnic identity tailoring - Kristina Romeike; Lilian Lechner; Hein de Vries; Anke Oenema (BMC, 2016)
Abstract Background Unhealthy dietary and physical activity (PA) patterns are highly prevalent in most Western countries, especially among lower-educated and ethnic minority groups. Therefore, interventions to promote healthy eating and physical activity that can reach large numbers of lower-educated people are needed. When developing interventions, the ethnic diversity of the lower-educated population may be taken into account to make intervention material more appealing to the target group. This article describes the development and evaluation of two computer-tailored nutrition and physical activity interventions for lower-educated Dutch, Turkish and Moroccan women. One version is tailored to sociocognitive variables (traditional tailoring), while the other is additionally tailored to ethnic identity (EI-tailoring). Method Using intervention mapping, two evidence- and theory-based interventions were developed. In the traditional tailoring intervention, messages are tailored to health behavior, awareness of own behavior, attitude and self-efficacy. The behavior change techniques used to address these factors are: descriptive and evaluative feedback, arguments, modeling, goal setting, planning, barrier identification and advice on how to deal with barriers, stimulating resistance to social pressure, mobilization of social support (nontailored), active learning (nontailored) and iterative feedback. In the EI-tailoring intervention, the material is additionally tailored to ethnic identity (EI). This means that recipients who feel strongly attached to their ethnic background receive different intervention material than recipients with a weak attachment to their background. This includes, for instance, the use of more traditional colors, role models that match with their origin and advice messages that refer to their ethnicity of origin. Discussion Developing an intervention that matches the needs of this specific target population was challenging due to the little evidence regarding the determinants of their health behavior, as well as the behavioral change techniques that have not been tested among Turkish and Moroccan women in the Netherlands before. Based on previous research among this and other target populations we hypothesize, however, that the determinants and strategies we use will be suitable. A randomized controlled trial will show whether the interventions are effective among our specific target group and whether EI-tailoring is beneficial. Trial registration Dutch Trial Registry NTR4506 , registration date: 1st may 2014